RANCANG BANGUN APLIKASI PENGAJUAN CUTI KARYAWAN BERBASIS WEB PADA PT. INDORAMA SYNTHETICS - Risa Nabilah Firmansyah; Yudhi Raymond Ramadhan; Candra Dewi Lestari (CV. Denasya Smart Publisher, 2025)
PT. Indo-Rama Synthetics Tbk is a company that manufactures Polyester Filament Yarns, “Polyester Stapel Fibers Pet Resin:, Polyester Chips and Polyester Filament Fabrics, where the company started commercial production in 1976 with a cotton spinning factory in Purwakarta which has around ± 1000 employees with various departments and positions. However, the leave application system is still manual. Where employees must make a written leave application and follow several processes that must be carried out. The design and development of the employee leave system uses the rapid application development software development method with stages (requirements planning, user design, construction and cutover), the design uses a unified modeling language (UML) with 4 (four) diagrams, namely use case diagrams, activity diagrams, sequence diagrams and class diagrams, program coding using the PHP framework Codeigniter. The results achieved from this study are an employee leave system for employees by providing several existing features including employee information, submission of leave for employees, and other menus. With the web and mobile based system, it is hoped that it will make it easier for employees to apply for leave.